2011
DOI: 10.1152/jn.00254.2011
|View full text |Cite
|
Sign up to set email alerts
|

The extent of interlimb transfer following adaptation to a novel visuomotor condition does not depend on awareness of the condition

Abstract: There is a controversy in the literature as to whether transfer of motor learning across the arms occurs because of an individual's cognitive awareness of the learned condition. The purpose of this study was to test whether the extent of interlimb transfer following adaptation to a novel visuomotor rotation with one arm, as well as the rate of learning acquired by the other arm, would vary depending on the subjects' awareness of the rotation condition. Awareness of the condition was varied by employing three e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
60
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 24 publications
(33 reference statements)
10
60
9
Order By: Relevance
“…Although intermanual transfer was observed previously (Halsband, 1992;Criscimagna-Hemminger et al, 2003;van Mier and Petersen, 2006;Wang et al, 2011), it was not found in the nonmirror task of the present study. This might have been because asymmetrical intermanual transfer occurred instead when using the symmetric mirror motor task (Kirsch and Hoffmann, 2010).…”
Section: Discussioncontrasting
confidence: 73%
“…Although intermanual transfer was observed previously (Halsband, 1992;Criscimagna-Hemminger et al, 2003;van Mier and Petersen, 2006;Wang et al, 2011), it was not found in the nonmirror task of the present study. This might have been because asymmetrical intermanual transfer occurred instead when using the symmetric mirror motor task (Kirsch and Hoffmann, 2010).…”
Section: Discussioncontrasting
confidence: 73%
“…For example, we have repeatedly observed the direct-effects of visuomotor adaptation with one arm on subsequent performance with the other arm (e.g., Lei and Wang 2014;Sainburg and Wang 2002;Wang and Sainburg 2006), although we often failed to observe after-effects in similar conditions that involved interlimb transfer (unpublished observations). The direct-effects observed in our studies indicate that initial visuomotor adaptation with one arm led to the formation of an internal model, because these effects are not influenced by the participants' cognitive awareness (Wang et al 2011; also see Taylor et al 2011). These findings and observations indicate that the aforementioned assumption may not be correct; more importantly, they also indicate that conclusions from a study could differ markedly, depending on whether they were based on direct-or after-effects data (e.g., substantial interlimb transfer based on direct-effects, no transfer based on after-effects).…”
supporting
confidence: 59%
“…However, as practice progressed actors began to make increasingly larger errors in the clockwise direction, meaning that they were overcompensating for the perturbation. The after-effects later demonstrated by the actor group were similar to a control actor group that was not provided with an explicit strategy (see also Wang et al 2011). These authors argued that implicit learning processes came to dominate explicit knowledge and awareness.…”
Section: Explicit Processes Encouraged Through Observationmentioning
confidence: 64%
“…However, observers showed no evidence of recognition unless sequences were observed in practice without the corresponding hand actions (see also Kelly et al 2003). Subsequently, Heyes and Foster (2002;also Bird and Heyes 2005) showed that observers were aware of the repetition in a short training sequence, in comparison with a longer sequence, but even in this former case, observational practice led to effector-specific learning, often taken as evidence that a more implicit, motor-based representation was acquired (yet see Wang et al 2011).…”
Section: Implicit Learning Through Observationmentioning
confidence: 99%